Navigating Financial Integrity: Gender Diversity in Boards as a Moderator in Indonesia’s Digital Economy - Alexander, Ferdinand Morin; Carolina, Yenni (Jurnal Riset Akuntansi dan Keuangan, 2024)
The rapid growth of Indonesia's digital economy has highlighted the need for transparent and accountable financial practices. This study examines the factors influencing earnings management practices in technology sector companies in Indonesia, focusing on top management compensation and audit quality, with gender diversity as a moderating variable. Using a quantitative descriptive approach, data from 16 tech companies over the period 2018-2023 were analyzed through panel regression. The findings indicate that top management compensation significantly affects earnings management practices, while audit quality shows a significant but positive impact, and gender diversity does not show a significant moderating effect. The results suggest that adequate compensation structures are essential for reducing earnings management practices, highlighting the need for improved audit standards and further exploration of gender diversity's role in corporate governance